GHK Peptide Inhibits Bleomycin-Induced Pulmonary Fibrosis in Mice by Suppressing TGFβ1/Smad-Mediated Epithelial-to-Mesenchymal Transition - Zhou, Xiao-Ming; Wang, Gui-Liang; Wang, Xiao-Bo; Liu, Li; Zhang, Qin; Yin, Yan; Wang, Qiu-Yue; Kang, Jian; Hou, Gang (Frontiers in Pharmacology, 2017)
Objective: Idiopathic pulmonary fibrosis is an irreversible and progressive fibrotic lung disease that leads to declines in pulmonary function and, eventually, respiratory failure and has no effective treatment. Gly-His-Lys (GHK) is a tripeptide involved in the processes of tissue regeneration and wound healing and has significant inhibitory effects on transforming growth factor (TGF)-β1 secretion. The effect of GHK on fibrogenesis in pulmonary fibrosis and the exact underlying mechanism underlying this effect have not been studied previously. Thus, this study investigated the effects of GHK on bleomycin (BLM)-induced fibrosis and identified the pathway that is potentially responsible for these effects. Methods: Intratracheal injections of 3 mg/kg BLM were administered to induce pulmonary fibrosis in C57BL/6 mice. GHK was administered intraperitoneally at doses of 2.6, 26 and 260 µg/ml/day every other day from the 4th to the 21st day after BLM instillation. Three weeks after BLM instillation, pulmonary injury and pulmonary fibrosis was evaluated by the hematoxylin-eosin (HE) and Masson’s trichrome (MT) staining. Chronic inflammation index was used for the histological assessments by two pathologists blindly to each other. Tumor necrosis factor(TNF)-ɑ and IL-6 levels in BALF and myeloperoxidase (MPO) activity in lung extracts were measured. For the pulmonary fibrosis evaluation, the fibrosis index calculated based on MT staining, collagen deposition and active TGF-β1 expression detected by ELISA, and the expression of TGF-β1, α-smooth muscle actin(SMA), fibronectin, MMP-9, and TIMP-1 by western blotting. The epithelial mesenchymal transition index, E-cadherin, and vimentin was also detected by western blot. The statistical analysis was performed by one-way ANOVA and the comparison between different groups were performed. Results: GHK suppresses BLM-induced fibrosis, chronic inflammation and epithelial-to-mesenchymal transition (EMT) in mice. Treatment with GHK at all three doses reduced inflammatory cell infiltration and interstitial thickness and attenuated BLM-induced pulmonary fibrosis in mice. GHK treatment significantly improved BLM-induced pathological changes, collagen deposition, and MMP-9/TIMP-1 imbalances in lung tissue and also reduced tumor necrosis factor (TNF)-ɑ, IL-6 expression in bronchoalveolar lavage fluid (BALF)and myeloperoxidase (MPO)MPO in lung extracts expression in bronchoalveolar lavage fluid (BALF). Furthermore, GHK reversed BLM-induced increases in TGF-β1, p-Smad2, p-Smad-3 and insulin-like growth factor-1 (IGF-1) expression.